Organ-On-A-Chip: A Survey of Technical Results and Problems - Danku, Alex Ede; Dulf, Eva-H; Braicu, Cornelia; Jurj, Ancuta; Berindan-Neagoe, Ioana (Frontiers in Bioengineering and Biotechnology, 2022)
Organ-on-a-chip (OoC), also known as micro physiological systems or ‘tissue chips’ have attracted substantial interest in recent years due to their numerous applications, especially in precision medicine, drug development and screening. Organ-on-a-chip devices can replicate key aspects of human physiology, providing insights into the studied organ function and disease pathophysiology. Moreover, these can accurately be used in drug discovery and for personalized medicine. These devices present useful substitutes to traditional preclinical cell culture methods and can reduce the use of in vivo animal studies. In the last few years OoC design technology has seen dramatic advances, leading to a wide range of biomedical applications. These advances have also revealed not only new challenges but also new opportunities. There is a need for multidisciplinary knowledge from the biomedical and engineering fields to understand and realize OoCs. The present review provides a snapshot of this fast-evolving technology, discusses current applications and highlights advantages and disadvantages for biomedical approaches.